2019
DOI: 10.3126/jucms.v7i2.27131
|View full text |Cite
|
Sign up to set email alerts
|

Role of Micro ESR in the Evaluation of Neonatal Sepsis

Abstract: INTRODUCTION: In a developing country like Nepal, where proper medical care and obstetrical facilities are still scarce in the rural areas, neonatal sepsis is a major cause of neonatal morbidity and mortality. With limited resources, early diagnosis and treatment if crucial, may not be achieved. Objective of this study is to evaluate the role of micro ESR in the diagnosis of neonatal sepsis. MATERIAL AND METHODS: A prospective analytical study was done where all neonates with suspected sepsis admitted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…Therefore, we added the test to our study. In our study, the median micro-ESR was 6.5(IQR =3-14); although the statistical association was not found as an alternative in diagnosis and in monitoring therapeutic progress [69,70]. Similar studies done in Nepal and India have shown the significance of micro-ESR levels concerning confirmed sepsis: Manandhar et al from Nepal found 17.3% of culture-confirmed sepsis had elevated ESR by 33.3%, while Ghaliyaz et al from India found 32% of culture-confirmed sepsis had elevated ESR by 38% [70,71].…”
Section: Discussioncontrasting
confidence: 76%
“…Therefore, we added the test to our study. In our study, the median micro-ESR was 6.5(IQR =3-14); although the statistical association was not found as an alternative in diagnosis and in monitoring therapeutic progress [69,70]. Similar studies done in Nepal and India have shown the significance of micro-ESR levels concerning confirmed sepsis: Manandhar et al from Nepal found 17.3% of culture-confirmed sepsis had elevated ESR by 33.3%, while Ghaliyaz et al from India found 32% of culture-confirmed sepsis had elevated ESR by 38% [70,71].…”
Section: Discussioncontrasting
confidence: 76%
“…A study done by Kafe R et al in Universal College of Medical Sciences, Bhairahawa, Nepal found 6% of babies with confrm sepsis and 12% had elevated micro –ESR level. 18 Similarly, a study done by Ghaliyah AZ et al in Yenepoya Medical College Teaching Hospital, Mangalore, India found 32% confrm sepsis with a 38% elevated micro-ESR level. 4 In our study also 13 (17.3%) babies had confrmed sepsis and a total of 25 (33.3%) babies had raised micro-ESR level showing the signifcance of micro-ESR level concerning confrm sepsis.…”
Section: Discussionmentioning
confidence: 93%
“…However, these tests are not easily available in our country and also not cost-efective. 18 Apart from other septic screening tests mentioned in Box 1, micro ESR is a single, cheap, easy to perform, less time consuming with sensitivity and specifcity of 63.3 % and 60% respectively. 19…”
Section: Discussionmentioning
confidence: 99%
“…13 Micro-ESR increased in 13/49 (26%) subjects. This result was higher than reported by Kafle et al 14 who found increase micro-ESR in 29/250 neonates (12%), while West et al 15 found that 406 neonates with sepsis, 251 (61.8%) subjects with increase micro-ESR (sensitivity of 75.7%) in the diagnosis of neonatal sepsis.…”
Section: Discussionmentioning
confidence: 54%